2018
DOI: 10.3892/ijmm.2018.3999
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV ameliorates high glucose‑induced renal tubular epithelial‑mesenchymal transition by blocking mTORC1/p70S6K signaling in HK‑2 cells

Abstract: Astragaloside IV (AST) is the major active saponin in Astragalus membranaceus and, reportedly, has a variety of pharmacological activities. However, the potential of AST to ameliorate high glucose-mediated renal tubular epithelial-mesenchymal transition (EMT) remains undetermined. The aim of the present research was to explore the effect and mechanism of AST in EMT of renal tubular epithelial cells, as an underlying mechanism of renal fibrosis and a vital feature involved in diabetic nephropathy. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…In addition, it has previously been reported that the epithetlial-mesenchymal transition (EMT) is significantly correlated with renal fibrosis, which is associated with calcineurin inhibitor-mediated nephrotoxicity (21). EMT is one of the basic mechanisms of renal fibrosis and involves various processes in which epithelial cells stop exhibiting epithelial characteristics, including the expression of E-cadherin, and obtain traits specific of mesenchymal cells, including the upregulation of α-SMA (25,47-48). In addition, it has previously been reported that vimentin is a potential novel biomarker in renal fibrosis (25,49).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has previously been reported that the epithetlial-mesenchymal transition (EMT) is significantly correlated with renal fibrosis, which is associated with calcineurin inhibitor-mediated nephrotoxicity (21). EMT is one of the basic mechanisms of renal fibrosis and involves various processes in which epithelial cells stop exhibiting epithelial characteristics, including the expression of E-cadherin, and obtain traits specific of mesenchymal cells, including the upregulation of α-SMA (25,47-48). In addition, it has previously been reported that vimentin is a potential novel biomarker in renal fibrosis (25,49).…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial-mesenchymal transition (EMT) of renal tubular epithelial cells is one of the underlying mechanisms of renal fibrosis, and encompasses a range of events whereby epithelial cells no longer exhibit certain epithelial traits, including E-cadherin expression. Instead, the cells acquire characteristics typical of mesenchymal cells, including the expression of α-SMA (30,31). In addition, vimentin has also been reported as a potential novel biomarker of renal fibrosis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Astragaloside (Gao et al, 2012;Gui et al, 2013;Wang et al, 2014;Xu et al, 2014a;Che et al, 2015;Wang et al, 2015d;Zhou et al, 2017b;Chen et al, 2018;Du et al, 2018;Ji et al, 2018;Chen et al, 2019b;Ju et al, 2019;Qu et al, 2019;Su et al, 2019;Wang et al, 2019c), calycosin (Tang et al, 2011; Tripterygium glycoside (Wan et al, 2010;Cheng et al, 2015a;Ma et al, 2015b;Wu et al, 2017;Gong et al, 2018;Zhan et al, 2019;Wang et al, 2020), triptolide (Gao et al, 2010;Yuan et al, 2011;Ma et al, 2013;Cao et al, 2015;Zhou et al, 2016;Dong et al, 2017;Li et al, 2017c;Liang et al, 2018;Yang et al, 2019b;Wan et al, 2020), celastrol (Yu et al, 2018;Zhang et al, 2019c) Puerarin (Kim et al, 2010;Zhong et al, 2014;Pan et al, 2015;Song et al, 2016;Zhou et a...…”
Section: Astragalus Mongholicus Bungementioning
confidence: 99%